Integration of Science and Parental Involvement in Islamic School Curriculum: A Review on Al-Azhar Islamic School Indonesia - Dardiri, Muhammad Amiruddin (UIN Mataram, 2024)
This article examines the integration of science and parental involvement within the Islamic school curriculum, with a particular focus on the implementation of Islamic Religious Education (Ind: Pendidikan Agama Islam [PAI]) at Al-Azhar Islamic School Solo Baru. The study employs a qualitative approach with a case study of Al-Azhar Islamic School Solo Baru. Data collection methods include interviews with religious education teachers, direct observations by the researcher, and documentation. After validating the data, an interactive analysis approach is used. The findings reveal that Al-Azhar Islamic School, as a pioneer in the modernisation of Islamic education in the 21st century, has successfully integrated religious and general education in a harmonious manner. The school does not merely use religion as a promotional tool, but actively implements and lives religious education in daily life. This achievement is particularly significant, considering that madrasas and Islamic boarding schools have traditionally focused on religious education and have yet to fully accommodate general education at the beginning of the 21st century. Abstrak: Artikel ini mengkaji integrasi sains dan keterlibatan orang tua dalam kurikulum sekolah Islam, dengan fokus pada implementasi Pendidikan Agama Islam (PAI) di Sekolah Islam Al-Azhar Solo Baru. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus di Sekolah Islam Al-Azhar Solo Baru. Teknik pengumpulan data dilakukan melalui wawancara dengan guru agama, observasi langsung oleh peneliti, dan dokumentasi. Setelah data diuji validitasnya, analisis dilakukan menggunakan pendekatan analisis interaktif. Hasil penelitian menunjukkan bahwa Sekolah Islam Al-Azhar, sebagai pelopor modernisasi pendidikan Islam abad ke-21, berhasil mengintegrasikan pendidikan agama dan pendidikan umum secara harmonis. Sekolah ini tidak hanya menjadikan agama sebagai alat promosi, tetapi juga mengimplementasikan dan menghidupkan pendidikan agama dalam kehidupan sehari-hari. Pencapaian ini sangat signifikan, mengingat bahwa madrasah dan pesantren masih cenderung fokus pada pendidikan agama dan belum sepenuhnya mengakomodasi pendidikan umum pada awal abad ke-21.